A Comparison of Strain-Based Methods for the Evaluation of the Relative Displacement of Beam-Like Structures - Kliewer, Kaitlyn; Glisic, Branko (Frontiers in Built Environment, 2019)
This research presents an evaluation and comparison of the various strain to displacement transformation methods for a beam-like structure. Displacements can provide useful information for the monitoring and assessment of structural performance, health, and safety. The displacement of a structure is correlated with the curvature of a structure, so any unusual behavior of the structure that alters the curvature will also affect the displacement of the structure. Additionally, monitoring the displacement of a structure is useful for evaluating service limits as excessive displacement are uncomfortable to users and can cause damage to surround structures. Direct displacement monitoring of a real-life structure can be challenging, especially for long-term measurements. Because of this, the focus of this research is on in-direct displacement monitoring based on strain sensors. Several methods to determine displacements from strain measurements have been presented in the literature; this paper provides a quantitative comparison of selected methods using both a static and dynamic analysis, providing the errors of the methods. The methods were applied in a small-scale laboratory test to a beam with fiber Bragg-grating strain sensors, with both static and dynamic loading cases. The experimental displacement results are compared to displacement results from LVDT displacement sensors. Finally, the methods are applied to an existing structure equipped with long-gauge fiber Bragg-grating strain sensors, an in-service highway overpass subjected to vehicle loading. The displacements for the overpass were obtained and compared with the service requirements.